Andrew Lloyd Webber's The Phantom of the Opera [videorecording (DVD)] - Lloyd Webber, Andrew, 1948- (Warner Home Video, 2005)
Tells the story of a disfigured musical genius who haunts the catacombs beneath the Paris Opera, waging a reign of terror over its occupants. When he falls fatally in love with Christine, the Phantom devotes himself to creating a new star for the Opera, exerting a strange sense of control over the young soprano as he nurtures her extraordinary talents.